Effect of Financial Literacy on Investment Interest (Case Study in Early Adult Age in Bandung City) - Sarah Raihana; Andrieta Shintia Dewi (Budapest International Research and Critics University, 2022)
The COVID-19 outbreak has had a significant impact and made major changes to the joints of life. In addition, suppressing Indonesia's economic growth includes affecting the finances of every generation, especially millennials. In the midst of the widespread lockdown and the spread of the COVID-19 virus throughout 2020, many investment opportunities emerged. There is a relationship between financial literacy and investment interest. Financial literacy has a positive influence on interest in investing and it can be concluded that financial literacy is known to have a significant influence on investment decisions. This study aims to examine the effect of financial literacy on investment interest in early adult age in the city of Bandung. The dependent variable is investment interest, while the independent variable is financial literacy. This research uses simple linear regression analysis. The results showed that financial literacy had a significant effect on investment interest. From this financial literacy, individuals will be able to use financial services and products correctly according to the needs they want and not be easily deceived by criminals who often take advantage of someone's ignorance of finances for personal gain. The role of financial literacy appears to be to provide understanding to early adults regarding investment.